A middle-Roman context from the public center of Bliesbrück (Sarreguemines, Department de la Moselle, France) - Bolzoni, Gloria (Rei Cretariae Romanae Fautorum Acta, 2017)
This article discusses a pottery assemblage found at the yet unnamed Gallo-Roman settlement, which developed in the territories of the small villages of Bliesbrück in Moselle and Reinheim in Saarland, on the border between France and Germany, in the valley of the Blies River, a tributary of the Saar. The wealth of archaeological finds from the surrounding territory witnesses a period of occupation that continues without interruption from the Bronze Age to the Middle Ages. On the same site, the European Archaeological Park of Bliesbruck-Reinheim was established in the 1990’s, thanks to the support of the Moselle Department, the French Ministry of Culture and the Landesdenkmalamt of the Saarland.